Mechanisms of hyoscine butylbromide to improve adenoma detection: A case-control study of surface visualization at simulated colonoscope withdrawal - East, James E.; Saunders, Brian P.; Burling, David; Tam, Emily; Boone, Darren; Halligan, Steve; Taylor, Stuart A. (Endoscopy International Open, 2015)
Background and study aims: Antispasmodics may improve mucosal visualization during colonoscope withdrawal, potentially improving polyp and adenoma detection. Meta-analysis and case-control studies suggest a 9 % to 13 % relative increase in adenoma and polyp detection. We aimed to assess the impact of hyoscine butylbromide on the expected visualization during colonoscope withdrawal using a CT colonography (CTC) simulation.Patients and methods: Datasets from a previous CTC study examining the effect of antispasmodic were re-analyzed with customised CTC software, adjusted to simulate a standard colonoscopic view. Eighty-six patients received intravenous (IV) hyoscine butylbromide 20 mg, 40 mg or no antispasmodic. Main outcome measurements at unidirectional flythrough, simulating colonoscope withdrawal, were percentage colonic surface visualization, numbers and sizes of unseen areas, and colonic length.Results: Use of antispasmodic was associated with a significant relative increase in percentage surface visualization of 2.6 % to 3.9 %, compared with no antispasmodic, P < 0.006. Total numbers of missed areas and intermediate sized (300 – 1000 mm2) missed areas were significantly decreased, by approximately 20 %. There were no differences between the 20-mg and 40-mg doses. Mean colonic length (161 – 169 cm) was unchanged by antispasmodic. Conclusions: IV hyoscine butylbromide at simulated colonoscope withdrawal was associated with significant increases in surface visualization, which might explain up to half the improvement in adenoma detection seen in clinical studies.